STRATEGI FUNDRAISING DALAM PENERIMAAN DANA ZIS PADA KANTOR LAYANAN LAZISMU WIROBRAJAN - Zuneiroh, Oktavia; Shofiyah, Indah (Universitas Negeri Surabaya, 2023)
This research was qualitative, with data collection through observation, interviews, and documentation. Data analyses used were data reduction, data presentation, and conclusion. This study aimed to determine the fundraising strategy carried out by the Lazismu Wirobrajan Service Office and to provide a more effective fundraising method. The results of this study indicated that there were fundraising strategies used by the Lazismu Wirobrajan Service Office i.e., a direct strategy (direct fundraising) and an indirect strategy (indirect fundraising). The direct fundraising strategies used included: direct mail, tele-fundraising, and face-to-face meetings. Meanwhile, the indirect fundraising strategies used by the Lazismu Wirobrajan Service Office were a social media campaign with Whatsapp and Instagram, as well as distributing brochures and holding events. The ideal strategy to carry out at the Lazismu Wirobrajan Service Office was to maximize social media as a means of fundraising (Digital Fundraising), especially in the rapidly growing digital era. This Digital Fundraising was used to carry out programs that had been defined in the work plan of the Lazismu Wirobrajan Service Office.